Strategy for the Development of Kampuang Minang Tourism Village in Nagari Sumpu, West Sumatra - Mandalia, Siska; Apriliana, Nadrah (Jurnal Ilmiah Poli Bisnis, 2023)
The study delves into crafting a holistic development plan for Kampuang Minang, a promising tourism village in Nagari Sumpu, West Sumatra, utilizing the SWOT analysis framework. It aims to identify the village's internal strengths and weaknesses while leveraging external opportunities and mitigating threats for sustainable tourism growth. Through an extensive SWOT analysis, the research uncovers Kampuang Minang's strengths in cultural heritage, natural beauty, and traditional practices. Using these findings, it proposes a strategic framework aligned with responsible tourism principles, emphasizing the preservation and promotion of local customs to offer authentic experiences. The strategy suggests investing in infrastructure and accommodations to address weaknesses and enhance visitor experiences. To seize opportunities and tackle threats, it emphasizes sustainable practices, positioning the village as an environmentally conscious destination. Marketing strategies are recommended to attract a diverse tourist base. Collaboratively designed with local stakeholders and experts, this strategy holds the potential to boost the village's economy while safeguarding its cultural and natural essence. Continuous monitoring and adaptation are crucial for its success and alignment with evolving community and industry needs.